Lean communication : applications for continuous process improvement - Yankelevitch, Sam. (Supply and operations management collection., 2015)
Four decades ago, the most progressive companies, particularly those in the manufacturing sector, embraced an aspirational notion stoically named Zero Defects. It was a broad corporate call to action in an era with no Internet, elongated supply chains, multicultural, multilingual, cross-generational work teams, or multiple time zones. It was to ensure that products would be better, work-related accidents down, and profits larger if people did not make mistakes. Today with the kaleidoscope of disruptive forces in business transactions, the speed of commerce and the ferocious level of competition for consumer loyalty and business survival--the cost of an enterprise's faulty communication can literally make or break a brand or product. There is now more than ever the urgency that how people connect to each other to move business forward must be foolproof.